Representasi Kekerasan terhadap Perempuan dalam Berpacaran pada Film Posesif - Septiana, Riska; ., Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
Cases of violence against women in Indonesia every year continues to grow. In the 2019 Annual notes, there were 406,178 cases of violence against women that were reported and handled during 2018. Film as a mass media that always delivers messages to the public by packaging issues and themes creatively makes films bring change and influence on people's lives both in mindset . The representations presented can be formed positively or negatively, where the representation reflects the ideological position when the film was created. With the type of descriptive research with a qualitative approach with a semiotic design, this study aims to determine the representation of violence against women in dating relationships that are portrayed through possessive films. The results of the study show that how possessive films represent acts of violence in courtship. This research uses John Fiske's semiotic method to find out the level, reality, level of representation and level of ideology. Data collection techniques in this research are documentation and study of literature. And supported by Standpoint Theory, Relational Maintenance Theory and Critical Theory. The results of this study are 8 scenes that represent forms of violence from several scenes represented through the environment, behavior, conversation, expression, gesture, camera, behavior, conflict, and character. The ideology that appears in possessive films is patriarchy which is shown from several scenes chosen by researchers.